ANALISIS BIPLOT KOMPONEN UTAMA PADA BANK UMUM (COMMERCIAL BANK) YANG BEROPERASI DI JAWA TENGAH - Ely Fitria Rifkhatussa'diyah; Hasbi Yasin; Agus Rusgiyono (Jurnal Gaussian, 2014)
Competition among banks in Indonesia nowadays are getting higher due to the good economic growth and increasing of middle social class in Indonesia. The number of banks cause high competition among banks and internal bank itselves. This high competition makes the management of the bank should think seriously to maintain its existence. In this case the assessment of the bank become very important in the banking business to survive in today's banking industry. This study was conducted to determine how competitive the Commercial Bank are operating in Central Java by a method of Principal Component Biplots. This analysis can be applied to find out information about the relative position, the similarity between objects and characteristic of variables in the three categories of commercial banks operating in Central Java based on their health aspects. The results of this study are the banks from each category have a distinct predominance in every aspect of health assessment variable. In addition, the biplots can give information on the variability more than 70% which means that principal component biplot explains the overall data well.